The Attitude of Islamic Religious Education Teachers Against the Implementation of Inclusive Education at the Elementary School Level - Amka Amka; Mirnawati Mirnawati (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the attitude of Islamic Religious Education teachers in elementary schools towards the implementation of inclusive education. The study used a non-experimental quantitative approach with a survey method. Subjects or informants in this study were teachers of Islamic Education who were scattered from 16 elementary schools in South Kalimantan. Data collection was carried out using questionnaires and interviews. Data were analyzed using descriptive statistics using percentages; teacher attitudes were assessed based on five criteria, namely excellent, good, sufficient, lacking, and very poor. These criteria adjust to the percentage range obtained. The results showed that the percentage of Islamic education teachers' attitudes towards the implementation of inclusive education in South Kalimantan was 67.18%, which was categorized as quite good. Several variables affect teacher attitudes in terms of gender, recent education, experience in training.